2002
DOI: 10.1128/jcm.40.5.1791-1797.2002
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a New Scheme for Typing Campylobacter jejuni and Campylobacter coli by PCR-Based Restriction Fragment Length Polymorphism Analysis

Abstract: A molecular typing approach for Campylobacter jejuni and Campylobacter coli was developed with restriction fragment length polymorphism analysis of a 9.6-kb PCR-amplified portion of the lipopolysaccharide gene cluster. Sixty-one Penner serotype reference strains were analyzed with this new genotyping scheme, and 32 genogroups were found. Eleven additional genogroups were obtained from 87 clinical C. jejuni strains tested. This molecular typing method shows a correlation with the Penner heat-stable serotyping m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
1
23
2
Order By: Relevance
“…In a previous study (20), a correlation between Penner serotypes and PCR-RFLP types and variations in the RFLP types of strains within a single Penner serotype were also observed. In addition to confirming these findings, our study demonstrated that the PCR-RFLP method is applicable to the typing and classification of NT strains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study (20), a correlation between Penner serotypes and PCR-RFLP types and variations in the RFLP types of strains within a single Penner serotype were also observed. In addition to confirming these findings, our study demonstrated that the PCR-RFLP method is applicable to the typing and classification of NT strains.…”
Section: Discussionmentioning
confidence: 99%
“…Ten NCTC reference strains were also included. The aim of the study was to see if there was a correlation between Penner HS serotypes and RFLP types, as previously described by Shi et al (20). We were especially interested in finding out if this method would be applicable to the serotyping of NT strains by genotypic means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOS gene (LG) typing scheme was established by PCRrestriction fragment length polymorphism of the wla gene cluster (11). Some of the genes in the same cluster were shown to be involved in protein glycosylation in C. jejuni strain 81-176 (12).…”
Section: Authors' Replymentioning
confidence: 99%
“…Sequencing of specific genes has shown to be highly efficient in the study of genetic variability of C. jejuni, specially gene fla A, which encodes the protein flagellin, the main monomeric subunit of the flagellum (7,9,14,15,21).…”
Section: Introductionmentioning
confidence: 99%